IMPROVING STUDENTS’ VOCABULARY MASTERY USING ENGLISH SONG - Intan Permata Sari; Elva Elvinna Asahra; Yana Yana (PROJECT (Professional Journal of English Education), 2019)
This research is a Classroom Research Action. The research aims to improve the tenth grade students of SMK Wirasaba Karawang in mastering vocabulary using English songs. Songs can be trusted to help remember vocabulary and used the songs are interested in learning English. Memorizing song can be used to develop English vocabulary mastery so that the purpose of learning English as a communication tool can be achieved optimally. It can be seen from the students’ score on vocabulary test which increased from three vocabulary tests given in the Cycle I and Cycle II. In the students’ achievement Cycle I was 67.33 and Cycle II was 83.7. It can be concluded that songs have a significant impact on improving students’ vocabulary mastery. Keywords: English song, vocabulary mastery, CAR